prove:
![1 - \cos(2theta) \div 1 + \cos(2theta) = \tan( {theta}^{2} ) 1 - \cos(2theta) \div 1 + \cos(2theta) = \tan( {theta}^{2} )](https://tex.z-dn.net/?f=1+-++%5Ccos%282theta%29++%5Cdiv+1+%2B++%5Ccos%282theta%29++%3D++%5Ctan%28+%7Btheta%7D%5E%7B2%7D+%29+)
Answers
Answered by
1
Step-by-step explanation:
plzzz give me brainliest ans and plzzzz follow me
Attachments:
![](https://hi-static.z-dn.net/files/d85/4508bc84f98315e2ab9b95d508d668ca.jpg)
Answered by
1
Answer:
Step-by-step explanation:
1 - Cos2θ/ 1 + Cos2θ
using identity Cos2θ = Cos²θ - Sin²θ = 2Cos²θ - 1 = 1 - 2Sin²θ.
= 1 - (1 - 2Sin²θ) / 1 + (2Cos²θ - 1)
= 1 - 1 + 2Sin²θ/ 1 - 1 + 2Cos²θ
= 2Sin²θ/2Cos²θ
= Tan²θ
= R.H.S.
Hence proved
Similar questions